Preparation method of wide-temperature-section wear-resistant protective coating of metal sealing surface and coating

By using composite electroplating technology to prepare a coating containing Co2+, ceramic particles and hBN particles on the surface of thin-walled metal seals, the problems of high surface roughness and insufficient wear resistance are solved, and high wear resistance and excellent sealing in a wide temperature range are achieved.

CN119710844AActive Publication Date: 2025-03-28BGRIMM ADVANCED MATERIALS SCI & TECH CO LTD

Patent Information

Application Number
CN202510014851.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-28
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The coating on the surface of existing thin-walled metal seals has problems such as excessive surface roughness and limited wear resistance, which leads to the problems of easy peeling of the coating, wear-through of the parts and poor sealing.

Method used

The coating was prepared under ultrasonic wave by composite electroplating technology, and a composite plating solution containing Co2+, ceramic particles and hBN particles was used to ensure uniform dispersion and high composite amount of ceramic particles and hBN particles through multi-stage composite plating.

Benefits of technology

The wear resistance of the coating is significantly improved and the surface roughness is reduced, and excellent sealing and wear resistance are maintained in a wide temperature range of -10°C to 600°C, so as to prevent thin-walled metal seals from being worn through.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710844A_ABST
    Figure CN119710844A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of coatings, and particularly relates to a preparation method of a wide-temperature-range wear-resistant protective coating of a metal sealing surface and the coating, and the method comprises the following steps: putting a pre-plated substrate into a plating solution with the Co < 2 + > concentration of 125g / L-155g / L, the ceramic particle concentration of chromium carbide particles and / or chromium oxide particles of 5g / L-15g / L and the hBN particle concentration of 1g / L-10 g / L, and electroplating under ultrasonic waves, the Dv50 values of the ceramic particles and the hBN particles are 2-8 [mu] m and 3-15 [mu] m respectively; the composite electroplating is divided into three stages, the ultrasonic frequencies of the three stages are 28-32 KHZ, 38-42 KHZ and 38-42 KHZ correspondingly, and the current densities of the three stages are 0.5-2 A / dm < 2 >, 1.5-3 A / dm < 2 > and 3-4 A / dm < 2 > correspondingly. The coating has significantly improved wear resistance and reduced surface roughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coatings, and in particular, relates to a preparation method of a wide temperature range wear-resistant protective coating for a metal sealing surface and the coating. Background Art

[0002] In order to improve the service life and operating temperature of various types of hot end components inside engines such as gas turbines and aircraft engines, wear-resistant and high-temperature resistant coatings have received great attention. Thin-walled metal seals with strong resilience are widely used in high-pressure compressors and high-pressure turbines of engines to improve their gas path sealing, but the above-mentioned thin-walled metal seals are susceptible to micro-wear during service, resulting in parts wear and reduced air tightness. It has been proposed to use thermal spraying technology to prepare CoCr-based coatings on the surface of thin-walled metal seals, but there are problems with poor sealing due to large surface roughness and easy peeling of the coating and wear and tear of parts due to limited wear resistance.

[0003] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the coating on the surface of thin-walled metal seals in the prior art, such as large surface roughness and limited wear resistance, which result in easy peeling of the coating, wear-through of parts and poor sealing, and to provide a method for preparing a wear-resistant protective coating for a metal sealing surface in a wide temperature range and a coating, which has significantly improved wear resistance and reduced surface roughness.

[0005] In order to achieve the above object, in a first aspect, the present invention provides a method for preparing a wide temperature range wear-resistant protective coating on a metal sealing surface, comprising the following steps:

[0006] The substrate is placed in a pre-plating solution for pre-plating to obtain a pre-plating layer; the substrate after the pre-plating treatment is placed in a composite plating solution for composite electroplating to obtain the wear-resistant protective coating, wherein the composite plating solution contains Co 2+ , ceramic particles and hBN particles, the ceramic particles include chromium carbide particles and / or chromium oxide particles, the particle size distribution of the ceramic particles is 2μm to 8μm, the particle size distribution of the hBN particles is 3μm to 15μm, and the Co in the composite plating solution is 2+ The concentration is 125g / L to 155g / L, the concentration of ceramic particles is 5g / L to 15g / L, and the concentration of hBN particles is 1g / L to 10g / L;

[0007] The composite electroplating is carried out under ultrasonic waves, and the composite electroplating includes first composite electroplating, second composite electroplating and third composite electroplating carried out in sequence. The ultrasonic frequency and current density of the first composite electroplating are 28KHZ-32KHZ and 0.5A / dm 2 ~2A / dm 2 The ultrasonic frequency and current density of the second composite electroplating are 38KHZ~42KHZ and 1.5A / dm 2 ~3A / dm 2 The ultrasonic frequency and current density of the third composite electroplating are 38KHZ~42KHZ, 3A / dm 2 ~4A / dm 2 .

[0008] In some preferred embodiments, the electroplating times of the first composite electroplating, the second composite electroplating, and the third composite electroplating are 1 h to 1.5 h, 1 h to 1.5 h, and 0.5 h to 1 h, respectively.

[0009] In some preferred embodiments, the temperature of the composite plating solution is 50°C to 60°C.

[0010] In some preferred embodiments, the composite plating solution further contains NaCl, H3BO3 and a first surfactant, the NaCl concentration in the composite plating solution is 30g / L-50g / L, the H3BO3 concentration is 20g / L-50g / L, the first surfactant concentration is 0.01g / L-0.2g / L, and the first surfactant is sodium dodecyl sulfate.

[0011] In some preferred embodiments, initial hBN particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain hBN particle precursors, and the hBN particle precursors are ultrasonically dispersed in a second surfactant aqueous solution and then centrifuged to obtain the hBN particles, wherein the second surfactant is sodium dodecyl sulfate;

[0012] And / or, initial ceramic particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain ceramic particle precursors, and the ceramic particle precursors are ultrasonically dispersed in water and then centrifuged to obtain the ceramic particles.

[0013] Preferably, the concentration of the second surfactant aqueous solution is 0.1 g / L-0.5 g / L.

[0014] In some preferred embodiments, the ceramic particles include chromium carbide particles; and / or, after the composite electroplating, heat treatment is performed to obtain the wear-resistant protective coating, and the heat treatment temperature is 400°C to 500°C.

[0015] In some preferred embodiments, the pre-plating solution is a nickel-based plating solution, wherein Ni 2+ The concentration is 45 g / L to 60 g / L, the pH of the pre-plating solution is 2 to 3.8, and the temperature of the pre-plating solution is 20° C. to 40° C.;

[0016] The current density of the pre-plating treatment is 3A / dm 2 ~9A / dm 2 , the time is 4min to 10min.

[0017] In a second aspect, the present invention provides a wear-resistant protective coating for a metal sealing surface over a wide temperature range, which is prepared by the preparation method described in the first aspect, wherein the wear-resistant protective coating comprises a Co matrix component and ceramic particles and hBN particles dispersed in the Co matrix component, wherein the ceramic particles comprise chromium carbide particles and / or chromium oxide particles.

[0018] In some preferred embodiments, the roughness of the wear-resistant protective coating is ≤1.2 μm.

[0019] The preparation method of the wear-resistant protective coating of the present invention comprises placing the pre-plated substrate into a 2+ The composite electroplating is carried out in a composite plating solution of chromium carbide ceramic particles and / or chromium oxide ceramic particles and hBN particles. The prepared coating includes a Co matrix component and ceramic particles and hBN particles dispersed in the Co matrix component. On the one hand, the good lubricity of the h-BN particles themselves can reduce the possibility of wear on the coating surface or adhesion of the grinding pair debris, and can also reduce the friction of the coating surface and improve the wear resistance. On the second hand, during high-temperature grinding shearing, the Co matrix component and the Cr element form a glaze layer to improve the lubricity and wear resistance of the coating. On the third hand, the strong pinning effect of a large number of chromium carbide ceramic particles and / or chromium oxide ceramic particles has the effect of refining the crystallization of the coating matrix metal and increasing the hardness of the coating. Through the mutual cooperation of the above three aspects, it is possible to maintain a low surface roughness and high wear resistance in a wide temperature range of -10℃ to 600℃, effectively resist micro-wear, prevent thin-walled metal seals from being worn through, and maintain excellent sealing.

[0020] In the composite plating solution, Co 2+When the concentration is 125g / L to 155g / L, the concentration of ceramic particles is 5g / L to 15g / L, the concentration of hBN particles is 1g / L to 10g / L, the particle size distribution of ceramic particles is 2μm to 8μm, and the particle size distribution of hBN particles is 3μm to 15μm, the composite electroplating is carried out under ultrasound, and the cavitation effect of ultrasound can make the ceramic particles and hBN particles in the plating solution evenly dispersed, and the composite electroplating is further carried out in stages. The ultrasonic frequency and current density of the first stage are 28KHZ to 32KHZ and 0.5A / dm 2 ~2A / dm 2 , using a lower ultrasonic frequency to improve the wettability of ceramic particles and hBN particles, achieving uniform dispersion of ceramic particles and hBN particles in the plating solution, and using a lower current density to perform preliminary co-deposition of ceramic particles, hBN particles and matrix metal Co, to obtain a matrix metal primer composite coating with a low particle composite amount, and to improve the bonding force between the composite coating and the substrate; the ultrasonic frequency and current density of the second stage are 38KHZ~42KHZ and 1.5A / dm 2 ~3A / dm 2 , using a higher ultrasonic frequency to further promote the uniform dispersion of ceramic particles and hBN particles, improve the uniform distribution of the coating, and at the same time increase the current density to promote the transmission speed of ceramic particles and hBN particles to the substrate, increase the composite amount of ceramic particles and hBN particles in the coating, and give full play to the role of chromium carbide ceramic particles and / or chromium oxide ceramic particles in promoting the crystallization refinement of the matrix metal; the ultrasonic frequency and current density of the third stage are 38KHZ~42KHZ, 3A / dm 2 ~4A / dm 2 , maintain the dispersion of ceramic particles and hBN particles in the plating solution, increase the current density to further increase the particle transfer speed, increase the composite amount of ceramic particles and hBN particles in the coating, give full play to the hBN particles to reduce the possibility of coating surface wear or adhesion to the grinding debris, Co matrix components and Cr elements form a glaze layer to improve the lubricity and wear resistance of the coating, and chromium carbide ceramic particles and / or chromium oxide ceramic particles to promote the refinement of matrix metal crystals. The three-stage composite electroplating under ultrasonic waves allows the above three aspects to cooperate with each other to maximize the reduction of coating roughness and improve coating wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 It is a schematic diagram of the cross-sectional structure of the wear-resistant protective coating for the metal sealing surface in a wide temperature range of the present invention.

[0023] Figure 2 This is a scanning electron microscope photograph of the surface morphology of the wear-resistant protective coating of Example 1 of the present invention.

[0024] Figure 3 This is a photograph of the appearance of the coating of Example 1 of the present invention after the fretting wear test at 400°C.

[0025] Figure 4 This is a photograph of the appearance of the coating of Comparative Example 4 of the present invention after the fretting wear test at 400°C.

[0026] Figure 5 This is a photograph of the appearance of the coating of Example 1 of the present invention after the fretting wear test at 500°C.

[0027] Figure 6 This is a photograph of the appearance of the coating of comparative example 4 of the present invention after the fretting wear test at 500°C. DETAILED DESCRIPTION

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] The inventors of the present invention have found that the coating on the surface of existing thin-walled metal seals has a large surface roughness and limited wear resistance, which easily leads to coating peeling, parts wear and tear, and affects the sealing performance.

[0030] In this first aspect, the present invention provides a method for preparing a wide temperature range wear-resistant protective coating on a metal sealing surface, comprising the following steps:

[0031] The substrate is placed in a pre-plating solution for pre-plating to obtain a pre-plating layer; the substrate after the pre-plating treatment is placed in a composite plating solution for composite electroplating to obtain the wear-resistant protective coating, wherein the composite plating solution contains Co 2+ , ceramic particles and hBN particles, the ceramic particles include chromium carbide particles and / or chromium oxide particles, the particle size distribution of the ceramic particles is 2μm to 8μm, the particle size distribution of the hBN particles is 3μm to 15μm, and the Co in the composite plating solution is 2+ The concentration is 125g / L to 155g / L, the concentration of ceramic particles is 5g / L to 15g / L, and the concentration of hBN particles is 1g / L to 10g / L;

[0032] The composite electroplating is carried out under ultrasonic waves, and the composite electroplating includes first composite electroplating, second composite electroplating and third composite electroplating carried out in sequence. The ultrasonic frequency and current density of the first composite electroplating are 28KHZ-32KHZ and 0.5A / dm 2 ~2A / dm 2 The ultrasonic frequency and current density of the second composite electroplating are 38KHZ~42KHZ and 1.5A / dm 2 ~3A / dm 2 The ultrasonic frequency and current density of the third composite electroplating are 38KHZ~42KHZ, 3A / dm 2 ~4A / dm 2 .

[0033] The preparation method of the wear-resistant protective coating of the present invention comprises placing the pre-plated substrate into a 2+ The composite plating is carried out in a composite plating solution containing chromium carbide ceramic particles and / or chromium oxide ceramic particles and hBN particles. The prepared coating includes a Co matrix component and ceramic particles and hBN particles dispersed in the Co matrix component. On the one hand, the good lubricity of the h-BN particles themselves can reduce the possibility of wear on the coating surface or adhesion of the grinding pair debris, and can also reduce the friction of the coating surface and improve the wear resistance. On the second hand, during high-temperature grinding shearing, the Co matrix component and the Cr element form a glaze layer to improve the lubricity and wear resistance of the coating. On the third hand, the strong pinning effect of a large number of chromium carbide ceramic particles and / or chromium oxide ceramic particles plays a role in the refinement of the crystallization of the coating matrix metal and increases the hardness of the coating. Through the mutual cooperation of the above three aspects, it can maintain a low surface roughness and high wear resistance in a wide temperature range of -10℃ to 600℃, effectively resist micro-wear, prevent thin-walled metal seals from being worn through, maintain excellent sealing, and improve the service life of parts.

[0034] In the composite plating solution of the present invention, Co 2+The concentration is not less than 125g / L, which can improve the current efficiency and prevent the problem of uneven coating or difficulty in forming the coating. It is not higher than 155g / L, which can prevent the cathode from polarizing and causing the current efficiency to decrease, and can improve the stability of the electrodeposition process. The concentration of ceramic particles is not less than 5g / L, which can increase the composite amount of ceramic particles in the coating, give full play to the role of chromium elements in forming a glaze layer and ceramic particles in promoting the crystallization and refinement of the matrix metal. It is not higher than 15g / L, which can prevent the accumulation of ceramic particles on the surface of the substrate and affect the mass transfer of matrix metal cobalt ions. The Dv50 value of ceramic particles is not less than 2μm, which can prevent the agglomeration of ceramic particles and affect the density and uniformity of the coating, and can give full play to the pinning effect of ceramic particles. It is not higher than 8μm, which can ensure The composite amount of ceramic particles in the coating can improve the wear resistance of the coating; the concentration of hBN particles is not less than 1g / L, which can increase the composite amount of hBN particles in the coating and give full play to the role of hBN particles in reducing the possibility of wear or adhesion of the coating surface to the grinding debris; it is not higher than 10g / L. On the one hand, it can prevent the accumulation of hBN particles on the surface of the substrate and affect the mass transfer of the matrix metal cobalt ions. On the other hand, it prevents the composite of ceramic particles from being affected, resulting in a decrease in the composite amount of ceramic particles and affecting the final wear resistance; the Dv50 value of hBN particles is not less than 3μm, which can prevent the agglomeration of hBN particles and thus affect the density and uniformity of the coating; it is not higher than 15μm, which can ensure the composite amount of hBN particles in the coating and prevent problems such as increased surface roughness of the coating and holes in the coating. In the composite plating solution, Co 2+ When the concentration is 125g / L to 155g / L, the concentration of ceramic particles is 5g / L to 15g / L, the concentration of hBN particles is 1g / L to 10g / L, the particle size distribution of ceramic particles is 2μm to 8μm, and the particle size distribution of hBN particles is 3μm to 15μm, the composite electroplating is carried out under ultrasound. Compared with magnetic stirring and other methods, it will not cause directional flow of the plating solution. The cavitation effect of ultrasound can make the ceramic particles and hBN particles in the plating solution uniformly dispersed, and the ceramic particles and HBN particles can be separated. Further, the composite electroplating is carried out in stages, and the ultrasonic frequency and current density of the first stage are 28KHZ to 32KHZ and 0.5A / dm 2 ~2A / dm 2 , using lower ultrasonic frequency to improve the wettability of ceramic particles and hBN particles, achieving uniform dispersion of ceramic particles and hBN particles in the plating solution, and using lower current density to perform preliminary co-deposition of ceramic particles, hBN particles and matrix metal Co to obtain a matrix metal primer composite coating with low particle composite content; the ultrasonic frequency and current density of the second stage are 38KHZ~42KHZ and 1.5A / dm 2 ~3A / dm 2, using a higher ultrasonic frequency to further promote the uniform dispersion of ceramic particles and hBN particles, improve the uniform distribution of the coating, and at the same time increase the current density to promote the transmission speed of ceramic particles and hBN particles to the substrate, increase the composite amount of ceramic particles and hBN particles in the coating, and give full play to the role of chromium carbide ceramic particles and / or chromium oxide ceramic particles in promoting the crystallization refinement of the matrix metal; the ultrasonic frequency and current density of the third stage are 38KHZ~42KHZ, 3A / dm 2 ~4A / dm 2 , maintain the dispersion of ceramic particles and hBN particles in the plating solution, increase the current density to further increase the particle transmission speed, increase the composite amount of ceramic particles and hBN particles in the coating, give full play to the hBN particles to reduce the possibility of coating surface wear or adhesion to the grinding debris, chromium elements to form a glaze layer, and chromium carbide ceramic particles and / or chromium oxide ceramic particles to promote the crystallization and refinement of the matrix metal. After the three-stage composite electroplating under ultrasonic waves, the above three aspects cooperate with each other to maximize the reduction of coating roughness and improve coating wear resistance.

[0035] If the ultrasonic frequency in the first stage is lower than 28KHZ, the uniform dispersion of ceramic particles and hBN particles in the plating solution will be affected. If it is higher than 32KHZ, the composite amount of ceramic particles and hBN particles will be too high, which will affect the connection between the composite coating and the substrate and the bonding force between the composite coating and the substrate. If the current density is lower than 0.5A / dm 2 , which will affect the mass transfer rate of the matrix metal cobalt ions, causing the coating matrix metal to grow too slowly, affecting the coating quality. If it is higher than 2A / dm 2 , the composite amount of ceramic particles and hBN particles is too high, which affects the bonding strength between the composite coating and the substrate; if the ultrasonic frequency of the second stage is lower than 38KHZ, it affects the full dispersion of ceramic particles and hBN particles in the plating solution, and affects the deposition and embedding of ceramic particles and hBN particles by the matrix metal; if it is higher than 42KHZ, it is easy to increase the bubbles in the plating solution, resulting in defects such as holes in the coating; if the current density is lower than 1.5A / dm 2 If the mass transfer rate of matrix metal ions is too low to catch up with the deposition rate of matrix metal ions, the composite amount of ceramic particles and hBN particles in the coating will be reduced, affecting the wear resistance of the coating. If the current density is higher than 3A / dm 2 The mass transfer rate of matrix metal ions is too fast, which is not conducive to the stable embedding deposition of ceramic particles and hBN particles, and is not conducive to the stable growth of the coating. If the ultrasonic frequency of the third stage is lower than 38KHZ, it will affect the composite amount of ceramic particles and hBN particles in the composite coating and the uniform distribution of ceramic particles and hBN particles in the coating. If it is higher than 42KHZ, it is easy to increase bubbles in the plating solution, resulting in defects such as holes in the coating. If the current density is lower than 3A / dm 2, which affects the composite amount of ceramic particles and hBN particles in the composite coating, and is not conducive to obtaining a coating with a high powder composite amount in a short time. If it is higher than 4A / dm 2 , which will cause the coating to be rough and produce defects such as holes. If only the first stage of small current and small ultrasonic frequency electroplating is used, the composite amount of ceramic powder and hBN particles in the coating is almost zero, and the wear resistance of the coating is insufficient. If only the second stage of current and ultrasonic frequency electroplating is used, it is easy to affect the bonding force between the composite coating and the substrate, resulting in a decrease in the wear resistance of the coating. If only the third stage of large current and large ultrasonic frequency electroplating is used, it is easy to cause the coating to be rough. If only the first stage of current and ultrasonic frequency electroplating and the second stage of current and ultrasonic frequency electroplating are used in sequence, it is easy to cause the overall composite amount of the coating to be low, reducing the wear resistance of the coating. If only the second stage of current and ultrasonic frequency electroplating and the third stage of current and ultrasonic frequency electroplating are used in sequence, it is easy to cause the bonding force between the coating and the substrate to be low, affecting the wear resistance of the coating. If only the first stage of current and ultrasonic frequency electroplating and the third stage of current and ultrasonic frequency electroplating are used in sequence, it is easy to cause the coating to be rough and affect the sealing of the parts.

[0036] The present invention places the substrate into a pre-plating solution for pre-plating treatment, which can improve the bonding force between the coating and the substrate and prevent the coating from peeling off.

[0037] The Dv50 values ​​of the ceramic particles of the present invention can be, for example, 2, 4, 6 and 8 μm, and the Dv50 values ​​of the hBN particles can be, for example, 3, 6, 9, 12 and 15 μm. 2+ The concentration can be, for example, 125, 130, 135, 140, 145, 150 and 155 g / L, the ceramic particle concentration can be, for example, 5, 7, 9, 11, 13 and 15 g / L, the hBN particle concentration can be, for example, 1, 3, 5, 7, 9 and 10 g / L, the ultrasonic frequency of the first composite electroplating can be, for example, 28, 29, 30, 31 and 32 KHZ, and the current density can be, for example, 0.5, 1, 1.5 and 2 A / dm 2 The ultrasonic frequency of the second composite electroplating can be, for example, 38, 39, 40, 41 and 42 KHZ, and the current density can be, for example, 1.5, 2, 2.5 and 3 A / dm 2 The ultrasonic frequency of the third composite electroplating can be, for example, 38, 39, 40, 41 and 42 KHZ, and the current density can be, for example, 3, 3.2, 3.4, 3.6, 3.8 and 4 A / dm 2 .

[0038] In some preferred embodiments, the electroplating times of the first composite electroplating, the second composite electroplating, and the third composite electroplating are 1 h to 1.5 h, 1 h to 1.5 h, and 0.5 h to 1 h, respectively. Under this preferred embodiment, the time of the first composite electroplating is not less than 1 hour, which is more conducive to promoting the growth of the coating and obtaining a coating with high bonding strength; the time of not more than 1.5 hours is more conducive to the subsequent growth of a coating with a high particle composite amount, and the time can be, for example, 1, 1.1, 1.2, 1.3, 1.4 and 1.5 hours; the time of the second composite electroplating is not less than 1 hour, which is more conducive to obtaining a coating with a good particle composite amount, which is convenient for supporting the wear resistance of the third composite electroplating coating; the time of not more than 1.5 hours is more conducive to avoiding the large deviation of the powder composite amount between the three stages affecting the uniformity of the overall composition of the coating, and the time can be, for example, 1, 1.1, 1.2, 1.3, 1.4 and 1.5 hours; the time of the third composite electroplating is not less than 0.5 hours, which is more conducive to obtaining a coating with a high particle composite amount of a certain thickness; the time of not more than 1 hour is more conducive to avoiding the roughness of the coating and the accumulation of powder affecting the wear resistance and powder composite amount of the coating, as well as improving the density of the coating, and the time can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9 and 1 hour.

[0039] In some preferred embodiments, the temperature of the composite plating solution is 50° C. to 60° C. In this preferred embodiment, the temperature of the composite plating solution is not less than 50° C., which is more conducive to promoting the transmission of ions in the plating solution, and the temperature is not higher than 60° C., which is more conducive to the stable preparation of the coating and reduces the roughness of the coating. The temperature of the composite plating solution can be, for example, 50° C., 52° C., 54° C., 56° C., 58° C. and 60° C.

[0040] In some preferred embodiments, the composite plating solution further contains NaCl, H3BO3 and a first surfactant, wherein the NaCl concentration in the composite plating solution is 30g / L-50g / L, the H3BO3 concentration is 20g / L-50g / L, the first surfactant concentration is 0.01g / L-0.2g / L, and the first surfactant is sodium dodecyl sulfate. Under this preferred embodiment, the composite plating solution contains NaCl, which improves the conductivity of the plating solution, is more conducive to the deposition of matrix metal cobalt ions, and the smooth progress of the electrodeposition process. The H3BO3 contained can buffer the pH value of the plating solution, which is more conducive to preventing the rapid decrease of the pH value of the plating solution after hydrogen precipitation. The surfactant contained is more conducive to the full wetting of the ceramic particles and hBN particles with the plating solution, promotes the dispersibility of the ceramic particles and hBN particles in the plating solution, and ensures the smooth progress of the electrodeposition process. Furthermore, the NaCl concentration is not less than 30g / L, which is more conducive to improving the conductivity of the plating solution, promoting the deposition of the matrix metal cobalt ions, and ensuring the smooth progress of the electrodeposition process. The deposition of particles is not higher than 50g / L, which is more conducive to improving the uniformity of current distribution, refining the coating crystallization and improving the coating quality. The concentration of H3BO3 is 20g / L-50g / L, which is more conducive to enhancing the pH buffering effect and improving the coating quality. The concentration of surfactant is not less than 0.01g / L, which is more conducive to improving the wettability of ceramic particles and hBN particles in the plating solution and preventing the agglomeration of ceramic particles and hBN particles from affecting the deposition of ceramic particles and hBN particles. It is not higher than 0.2g / L, which is more conducive to avoiding turbidity of the plating solution, improving the stability of the plating solution and reducing the roughness of the coating.

[0041] In some preferred embodiments, initial hBN particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain a hBN particle precursor, and the hBN particle precursor is ultrasonically dispersed in a second surfactant aqueous solution and then centrifuged to obtain the hBN particles, wherein the second surfactant is sodium dodecyl sulfate;

[0042] And / or, initial ceramic particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain ceramic particle precursors, and the ceramic particle precursors are ultrasonically dispersed in water and then centrifuged to obtain the ceramic particles.

[0043] Under this preferred scheme, after the initial hBN particles are ultrasonically dispersed and separated in anhydrous ethanol, they are ultrasonically dispersed in an aqueous surfactant solution, which is more conducive to improving the wettability of the hBN particles, so that the hBN particles are fully dispersed in the composite plating solution, and after composite electroplating, they are evenly distributed in the coating, thereby improving the density of the coating. The second surfactant is sodium dodecyl sulfate, which is more conducive to improving the wettability of the hBN particles. At the same time, it is consistent with the first surfactant in the plating solution, and no other surfactants are introduced into the plating solution, thereby improving the stability of the plating solution. After the initial ceramic particles are ultrasonically dispersed and separated in anhydrous ethanol, they are ultrasonically dispersed and separated in water, which is more conducive to improving the wettability of the ceramic particles, so that the ceramic particles are fully dispersed in the composite plating solution, and after composite electroplating, they are evenly distributed in the coating, thereby improving the density of the coating.

[0044] Preferably, the concentration of the second surfactant aqueous solution is 0.1 g / L-0.5 g / L. Under this preferred embodiment, it is more conducive to improving the wettability of hBN particles and preventing agglomeration of hBN particles. The concentration of the second surfactant aqueous solution can be, for example, 0.1, 0.2, 0.3, 0.4 and 0.5 g / L.

[0045] In some preferred embodiments, the ceramic particles include chromium carbide particles; and / or, after the composite electroplating, heat treatment is performed to obtain the wear-resistant protective coating, and the temperature of the heat treatment is 400° C. to 500° C. In this preferred embodiment, the ceramic particles include chromium carbide particles, which have a higher hardness than chromium oxide, so that the coating has a high hardness, which is more conducive to enhancing the wear resistance of the coating.

[0046] In some preferred embodiments, the pre-plating solution is a nickel-based plating solution, wherein Ni 2+ The concentration is 45 g / L to 60 g / L, the pH of the pre-plating solution is 2 to 3.8, and the temperature of the pre-plating solution is 20° C. to 40° C.;

[0047] The current density of the pre-plating treatment is 3A / dm 2 ~9A / dm 2 , the time is 4min to 10min.

[0048] In this preferred embodiment, the pre-plating solution is a nickel-based plating solution, and the pre-plating layer is a nickel-based plating layer, which is more conducive to improving the bonding strength between the coating and the substrate and improving the service life of the coating. 2+The concentration is not less than 45g / L, which is more conducive to improving the current efficiency and promoting the smooth progress of the electrodeposition process. It is not higher than 60g / L, which is more conducive to avoiding the increase of the roughness of the coating due to the excessive precipitation of nickel ions. The pH of the pre-plating solution is not less than 2, which is more conducive to avoiding the deposition and precipitation of nickel ions due to the increase of hydrogen evolution reaction. The pH is not higher than 3.8, which is more conducive to improving the current efficiency of the plating solution and improving the stability of the plating solution. The temperature of the pre-plating solution is not less than 20°C, which is more conducive to the transmission of nickel ions and the smooth progress of the electrodeposition process. The temperature is not higher than 40°C, which is more conducive to controlling the progress of the ion reaction and reducing the roughness of the coating. Based on the above-mentioned pre-plating solution, the current density of the pre-plating treatment is not less than 3A / dm 2 , which is more conducive to the rapid deposition of nickel plating, no higher than 9A / dm 2 , which is more conducive to reducing the roughness of the coating. Furthermore, the pre-plating time is not less than 4 minutes, which is more conducive to the growth of the nickel base layer, and not more than 10 minutes, which is more conducive to leaving a larger growth space for the cobalt-based composite coating. 2+ The concentration can be, for example, 45, 48, 51, 54, 57 and 60 g / L, the pH of the pre-plating solution can be, for example, 2, 2.3, 2.6, 2.9, 3.2, 3.6 and 3.8, the temperature of the pre-plating solution can be, for example, 20, 25, 30, 35 and 40° C., and the current density of the pre-plating treatment can be, for example, 3, 4, 5, 6, 7, 8 and 9 A / dm 2 The time can be, for example, 4, 5, 6, 7, 8, 9 and 10 minutes.

[0049] In a second aspect, the present invention provides a wide temperature range wear-resistant protective coating for metal sealing surfaces, which is prepared by the preparation method described in the first aspect, and the wear-resistant protective coating includes a Co matrix component and ceramic particles and hBN particles dispersed in the Co matrix component, and the ceramic particles include chromium carbide particles and / or chromium oxide particles. The h-BN particles of the coating themselves have good lubricity, and the Co matrix component and Cr element of the coating form a glaze layer during high-temperature abrasion and shearing. The chromium carbide ceramic particles and / or chromium oxide ceramic particles increase the hardness of the coating, and the coating has significantly improved wear resistance and reduced surface roughness. The cross-sectional structure of the wear-resistant protective coating of the present invention refers to Figure 1 .

[0050] In some preferred embodiments, the roughness of the wear-resistant protective coating is ≤1.2 μm.

[0051] The present invention is further described in detail below with reference to specific embodiments.

[0052] Example 1

[0053] A method for preparing a wide temperature range wear-resistant protective coating for a metal sealing surface, comprising the following steps:

[0054] Step 1: ultrasonically disperse the initial hBN particles in anhydrous ethanol for 3 minutes and then centrifuge to obtain a hBN particle precursor, ultrasonically disperse the hBN particle precursor in a sodium dodecyl sulfonate aqueous solution (aqueous solution of a second surfactant) for 3 minutes and then centrifuge, repeat the process of ultrasonically dispersing in the sodium dodecyl sulfonate aqueous solution and then centrifuging 3 times to obtain hBN particles for standby use, the concentration of the sodium dodecyl sulfonate aqueous solution is 0.3 g / L, and the Dv50 value of the hBN particles is 10 μm; ultrasonically disperse the initial chromium carbide ceramic particles in anhydrous ethanol for 3 minutes and then centrifuge to obtain a chromium carbide ceramic particle precursor, ultrasonically disperse the chromium carbide ceramic particle precursor in water for 3 minutes and then centrifuge, repeat the process of ultrasonically dispersing in water and then centrifuging 3 times to obtain chromium carbide ceramic particles for standby use, and the Dv50 value of the chromium carbide ceramic particles is 6 μm;

[0055] Step 2: Place the substrate in a nickel-based pre-plating solution and use a nickel anode for pre-plating to obtain a pre-plating layer. 2+ The concentration is 50g / L, the pre-plating solution temperature is 25℃, the pre-plating solution pH is 2.5, and the current density is 6A / dm 2 , the pre-plating time is 8min;

[0056] Step 3: Place the substrate with the pre-plated layer after the pre-plating treatment in step 2 into a composite plating solution, and use a cobalt plate for composite electroplating to obtain a wear-resistant protective coating. The composition of the composite plating solution is Co 2+ : 140g / L, NaCl: 45g / L, H3BO3: 35g / L, sodium dodecyl sulfonate (first surfactant): 0.1g / L, chromium carbide ceramic particles obtained in step 1: 10g / L, hBN particles obtained in step 1: 5g / L, the temperature of the composite plating solution is 55°C, the composite electroplating is carried out under ultrasound, and the composite electroplating is carried out in sequence as the first composite electroplating, the second composite electroplating and the third composite electroplating, the ultrasonic frequency of the first composite electroplating is 30KHZ, and the current density is 0.5A / dm 2 The electroplating time is 1h, the ultrasonic frequency of the second composite electroplating is 40KHZ, and the current density is 2A / dm 2 The electroplating time is 1.5h, the ultrasonic frequency of the third composite electroplating is 40KHZ, and the current density is 3A / dm 2 , the electroplating time is 0.5h.

[0057] A wear-resistant protective coating is prepared by the above-mentioned preparation method, and the surface morphology of the coating is shown in Figure 2 , dispersed chromium carbide ceramic particles and hBN particles are uniformly dispersed in the Co matrix component.

[0058] Example 2

[0059] The preparation method of Example 1 is referred to, except that in step 3, the electroplating time of the third composite electroplating is 1.5 hours. In the prepared wear-resistant protective coating, chromium carbide ceramic particles and hBN particles are dispersed in the Co matrix component.

[0060] Example 3

[0061] The preparation method of Example 1 is referred to, except that in step 3, the temperature of the composite plating solution is 45° C. In the prepared wear-resistant protective coating, chromium carbide ceramic particles and hBN particles are dispersed in the Co matrix component.

[0062] Example 4

[0063] The preparation method of Example 1 is referred to, except that in step 3, there is no sodium dodecyl sulfate in the composite plating solution, and the first surfactant is not used. In the prepared wear-resistant protective coating, chromium carbide ceramic particles and hBN particles are dispersed in the Co matrix component, and the hBN particles are agglomerated.

[0064] Example 5

[0065] The preparation method of Example 1 is referred to, except that in step 3, the concentration of NaCl in the composite plating solution is 60 g / L. The wear-resistant protective coating prepared has chromium carbide ceramic particles and hBN particles dispersed in the Co matrix component, and the cobalt matrix metal grains in the coating are coarse.

[0066] Example 6

[0067] The preparation method of Example 1 is referred to, except that in step 3, the NaCl concentration in the composite plating solution is 20 g / L. In the prepared wear-resistant protective coating, chromium carbide ceramic particles and hBN particles are dispersed in the Co matrix component.

[0068] Example 7

[0069] The preparation method of Example 1 is referred to, except that chromium oxide ceramic particles are used instead of chromium carbide ceramic particles. In the prepared wear-resistant protective coating, chromium oxide ceramic particles and hBN particles are dispersed in the Co matrix component.

[0070] Comparative Example 1

[0071] The preparation method of Example 1 is referred to, except that in step 3, only the first composite electroplating is performed, and the time of the first composite electroplating is 3.5 hours. In the prepared wear-resistant protective coating, chromium carbide ceramic particles and hBN particles are distributed in the Co matrix component.

[0072] Comparative Example 2

[0073] The preparation method of Example 1 is referred to, except that in step 3, only the third composite electroplating is performed, and the time of the third composite electroplating is 3.5 hours. The prepared wear-resistant protective coating is rough, and chromium carbide ceramic particles and hBN particles are distributed in the Co matrix component.

[0074] Comparative Example 3

[0075] Referring to the preparation method of Example 1, the difference is that in step 3, only the first composite electroplating and the third composite electroplating are performed, the time of the first composite electroplating is 1.5 hours, and the time of the third composite electroplating is 2 hours. The wear-resistant protective coating prepared has chromium carbide ceramic particles and hBN particles distributed in the Co matrix component.

[0076] Comparative Example 4

[0077] Referring to the preparation method of Example 1, the difference is that in step 3, the order of the first composite electroplating, the second composite electroplating and the third composite electroplating is different, and the first composite electroplating, the third composite electroplating and the second composite electroplating are performed in sequence. The wear-resistant protective coating prepared has chromium carbide ceramic particles and hBN particles distributed in the Co matrix component.

[0078] The coatings of the embodiment and the comparative example were tested for surface roughness (GB / T 1031) using a SJ-210 surface roughness tester. The roughness was measured at least 3 different positions and the average value was obtained. The test results are shown in Table 1. The coatings of the embodiment and the comparative example were tested for fretting wear performance at 400°C and 500°C using a step load method. The test parameters are shown in Table 2. The test results are shown in Table 1. The wear value was obtained by testing with a white light interferometer. The appearance of the coating of Example 1 after the fretting wear test at 400°C is shown in Table 2. Figure 3 , the appearance photos after 500℃ fretting wear test are shown in Figure 5 The appearance of the coating of Comparative Example 4 after the fretting wear test at 400°C is shown in Figure 4 , the appearance photos after 500℃ fretting wear test are shown in Figure 6 .

[0079] Table 1

[0080]

[0081] Table 2

[0082] Serial number Temperature / ℃ Frequency / Hz Load / N Time / s 1 400 / 500 5 10 1001 2 400 / 500 5 20 1001 3 400 / 500 5 30 1001 4 400 / 500 5 40 1001 5 400 / 500 5 50 1001 6 400 / 500 5 60 1001 7 400 / 500 5 70 1001 8 400 / 500 5 80 1001 9 400 / 500 5 90 1001 10 400 / 500 5 100 1001

[0083] Comparing Comparative Example 1 with Example 1, compared with electroplating using only the process parameters of the first composite electroplating, the first composite electroplating, the second composite electroplating and the third composite electroplating are performed in sequence, which can increase the composite amount of chromium carbide ceramic particles and hBN particles, and improve the wear resistance of the coating. Comparing Comparative Example 2 with Example 1, compared with electroplating using only the process parameters of the third composite electroplating, the first composite electroplating, the second composite electroplating and the third composite electroplating are performed in sequence, which can reduce the roughness of the coating and improve the wear resistance of the coating. Comparing Comparative Example 3 with Example 1, compared with electroplating using only the process parameters of the third composite electroplating, the first composite electroplating, the second composite electroplating and the third composite electroplating are performed in sequence, which can reduce the roughness of the coating and improve the wear resistance of the coating. The process parameters of the first composite electroplating and the third composite electroplating are used for electroplating for the first time, and the first composite electroplating, the second composite electroplating and the third composite electroplating are performed in sequence, which can reduce the roughness of the coating and improve the wear resistance of the coating. Comparing Comparative Example 4 and Example 1, compared with first electroplating with the process parameters of the first composite electroplating, then electroplating with the process parameters of the third composite electroplating, and then electroplating with the process parameters of the second composite electroplating, the first composite electroplating, the second composite electroplating and the third composite electroplating are performed in sequence, which can improve the wear resistance of the coating and reduce the roughness of the coating.

[0084] Comparing Example 1 and Example 2, the time of the third composite electroplating is not more than 1h, which is more conducive to reducing the roughness of the coating and improving the wear resistance of the coating. Comparing Example 1 and Example 3, the temperature of the composite plating solution is not less than 50°C, which is more conducive to reducing the roughness of the coating and improving the wear resistance of the coating. Comparing Example 1 and Example 4, the composite plating solution contains a surfactant, which is more conducive to reducing the roughness of the coating, increasing the composite amount of chromium carbide ceramic particles and hBN particles, and improving the wear resistance of the coating. Comparing Example 1 and Example 5, the NaCl concentration in the composite plating solution is not higher than 50g / L, which is more conducive to crystallization refinement of the coating matrix metal, reducing the roughness of the coating, and improving the wear resistance of the coating. Comparing Example 1 and Example 6, the NaCl concentration in the composite plating solution is not less than 30g / L, which is more conducive to increasing the composite amount of chromium carbide ceramic particles and hBN particles, improving the wear resistance of the coating, and reducing the roughness of the coating. Comparing Example 1 and Example 7, the use of chromium carbide ceramic particles is more conducive to improving the wear resistance of the coating.

[0085] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a wide temperature range wear-resistant protective coating for a metal sealing surface, characterized in that: The following steps are involved: The substrate is placed in a pre-plating solution for pre-plating to obtain a pre-plating layer; the substrate after the pre-plating treatment is placed in a composite plating solution for composite electroplating to obtain the wear-resistant protective coating, wherein the composite plating solution contains Co 2+ , ceramic particles and hBN particles, the ceramic particles include chromium carbide particles and / or chromium oxide particles, the particle size distribution of the ceramic particles is 2μm to 8μm, the particle size distribution of the hBN particles is 3μm to 15μm, and the Co in the composite plating solution is 2+ The concentration is 125g / L to 155g / L, the concentration of ceramic particles is 5g / L to 15g / L, and the concentration of hBN particles is 1g / L to 10g / L; The composite electroplating is carried out under ultrasonic waves, and the composite electroplating includes first composite electroplating, second composite electroplating and third composite electroplating carried out in sequence. The ultrasonic frequency and current density of the first composite electroplating are 28KHZ-32KHZ and 0.5A / dm 2 ~2A / dm 2 The ultrasonic frequency and current density of the second composite electroplating are 38KHZ~42KHZ and 1.5A / dm 2 ~3A / dm 2 The ultrasonic frequency and current density of the third composite electroplating are 38KHZ~42KHZ, 3A / dm 2 ~4A / dm 2 .

2. The preparation method according to claim 1, characterized in that: The electroplating times of the first composite electroplating, the second composite electroplating and the third composite electroplating are 1 h to 1.5 h, 1 h to 1.5 h and 0.5 h to 1 h respectively.

3. The preparation method according to claim 1, characterized in that: The temperature of the composite plating solution is 50°C to 60°C.

4. The preparation method according to claim 1, characterized in that: The composite plating solution also contains NaCl, H3BO3 and a first surfactant. The NaCl concentration in the composite plating solution is 30g / L-50g / L, the H3BO3 concentration is 20g / L-50g / L, the first surfactant concentration is 0.01g / L-0.2g / L, and the first surfactant is sodium dodecyl sulfate.

5. The preparation method according to claim 1, characterized in that: The initial hBN particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain a hBN particle precursor, and the hBN particle precursor is ultrasonically dispersed in a second surfactant aqueous solution and then centrifuged to obtain the hBN particles, wherein the second surfactant is sodium dodecyl sulfate; And / or, initial ceramic particles are ultrasonically dispersed in anhydrous ethanol and then centrifuged to obtain ceramic particle precursors, and the ceramic particle precursors are ultrasonically dispersed in water and then centrifuged to obtain the ceramic particles.

6. The preparation method according to claim 5, characterized in that: The concentration of the second surfactant aqueous solution is 0.1 g / L-0.5 g / L.

7. The preparation method according to claim 1, characterized in that: The ceramic particles include chromium carbide particles; and / or, after the composite electroplating, heat treatment is performed to obtain the wear-resistant protective coating, and the temperature of the heat treatment is 400°C to 500°C.

8. The preparation method according to claim 1, characterized in that: The pre-plating solution is a nickel-based plating solution. 2+ The concentration is 45 g / L to 60 g / L, the pH of the pre-plating solution is 2 to 3.8, and the temperature of the pre-plating solution is 20° C. to 40° C.; The current density of the pre-plating treatment is 3A / dm 2 ~9A / dm 2 , the time is 4min to 10min.

9. A wide temperature range wear-resistant protective coating for metal sealing surfaces, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The wear-resistant protective coating comprises a Co matrix component and ceramic particles and hBN particles dispersed in the Co matrix component, wherein the ceramic particles comprise chromium carbide particles and / or chromium oxide particles.

10. The wear-resistant protective coating according to claim 9, characterized in that: The roughness of the wear-resistant protective coating is ≤1.2 μm.

Citation Information

Patent Citations

  • Preparation method of high-temperature protective coating and coating

    CN117144278A

  • Composite plating and method thereof

    JP1990236300A

  • EMI shielding conductive thin film using dry-wet plating and method for preparing the same

    KR101003317B1

  • Method of depositing a wear resistant seal coating and seal system

    US20040185294A1

  • Wear-resistant coating produced by electrodeposition and process therefor

    US20150075327A1

Cited By

  • Preparation method of active cutting cobalt-based coating and coating

    CN121295289A